Ocular manifestations and its associated factors in patients with dermatitis at a tertiary care hospital in Kathmandu - Rizyal, Aparna; Pathak, Deeptara; Manandhar, Roji (Nepal Medical College Journal, 2022)
Dermatitis also known as eczema, is inflammation of the skin, typically characterized by itchiness, redness and a rash. Dermatitis was estimated to affect 245 million people globally in 2015 or 3.34% of the world population. In Nepal, studies from different parts of the country have reported the prevalence of dermatitis between 15.9 to 39.2%. Severe dermatitis with repeated scratching and rubbing of the face predisposes the patient to various ocular complications. A hospital-based, cross-sectional, descriptive study was conducted to assess the overall frequency and type of ophthalmological complications among patients with dermatitis at a tertiary care hospital in Kathmandu. A total of 91 patients were enrolled for this study. The minimum age was 5 years and maximum was 78 years, with the mean of 30.48 with a standard deviation of ± 20.28. The upper and lower limits for estimated mean age were 34.63 years to 26.33 years at 95% confidence interval. Seventy-one (78.0%) of all patients had ocular manifestations, many of them had more than one manifestation. Females outnumbered the males (41.8%; 36.3%) with respect to the occurrence of ocular manifestations in dermatitis. The commonest ocular manifestations were blepharitis in 35 (38.5%) patients, followed by eyelid eczema in 13 (14.3%) patients, allergic conjunctivitis in 5 (5.5%) and patients with other manifestations. Based on professional classification, over one fourth of the participants were students accounting for 44.0%, followed by homemakers accounting for 23.1% and shopkeepers accounting for 11.1%, respectively. A statistically significant association was observed with the ocular manifestation in relation to gender (p value=0.03) and occupation (p value=0.03). However, no association was observed between ocular manifestation with duration of dermatitis (p value=0.65), type of dermatitis (p value=0.94), personal and family history of allergy/atopy (pvalues=0.26; 0.58, respectively).